2006
DOI: 10.1161/circulationaha.106.626143
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Left Ventricular Size and Function

Abstract: Background-Cardiac CT (CCT) and real-time 3D echocardiography (RT3DE) are being used increasingly in clinical cardiology. CCT offers superb spatial and contrast resolution, resulting in excellent endocardial definition. RT3DE has the advantages of low cost, portability, and live 3D imaging without offline reconstruction. We sought to compare both CCT and RT3DE measurements of left ventricular size and function with the standard reference technique, cardiac MR (CMR). Methods and Results-In 31 patients, RT3DE da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
87
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 417 publications
(98 citation statements)
references
References 35 publications
8
87
2
1
Order By: Relevance
“…Today, this modality provides multiplane dynamic images of the beating heart with excellent spatial resolution and temporal resolution of 30 phases per cardiac cycle, which is comparable to what has been for many years the standard frame rate in 2D echocardiography. The combination of these features places CMR imaging as the tentative "gold standard" for LV size and function, as reflected by multiple publications in which it was used as such to validate other noninvasive techniques (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, this modality provides multiplane dynamic images of the beating heart with excellent spatial resolution and temporal resolution of 30 phases per cardiac cycle, which is comparable to what has been for many years the standard frame rate in 2D echocardiography. The combination of these features places CMR imaging as the tentative "gold standard" for LV size and function, as reflected by multiple publications in which it was used as such to validate other noninvasive techniques (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…trast resolution that has become the standard reference in the assessment of left ventricular (LV) size and function (1,2), against which other techniques are frequently validated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, this technique relies on the detection of endocardial boundaries, which requires frame-by-frame manual tracing on multiple slices, and is thus of limited value in clinical practice.…”
mentioning
confidence: 99%
“…Validation of the analysis of left ventricular ejection fraction and volumes using RT-3D-Echo has been demonstrated in previous studies that used magnetic resonance imaging (MRI) [8][9][10][11] . However, MRI has limitations regarding patients with mechanical prosthesis, pacemakers, metallic devices, or those who are obese or have difficulty to stay in small physical spaces.…”
mentioning
confidence: 89%
“…In this context, another investigational imaging method -the 64-slice ultrafast computed tomography (CT), has been used for the structural analysis of the heart, especially of the coronary anatomy. The 64-slice CT provides a better anatomical analysis in relation to echocardiography, whereas the echocardiographic analysis allows better temporal identification in relation to CT. Few studies in the literature have compared echocardiography with CT for the assessment of left ventricular ejection fraction and volumes [11][12][13][14] . Thus, the objective of this study was to compare left ventricular ejection fraction and volumes as measured by RT-3D-Echo and ultrafast 64-slice CT.…”
mentioning
confidence: 99%
“…The recently validated RT3DE volumetric quantification of global and regional LV function 88 overcomes limitations of 2D echocardiography as it eliminates geometric assumptions, identifies the true LV apex and evaluates wall motion encompassing all planes 89 . Jenkins, et al 90 demonstrated the correlation of RT3DE to MRI with lower intra and inter observer variability, whilst comparing it to computed tomography, Sugeng, et al 91 have shown its superiority in LVEF and volume measurement. RT3DE can assess LV dyssynchrony and demonstrated a greater improvement from CRT with RT3DE guided LV lead placement 92 .…”
Section: Newer Parameters and Applicationmentioning
confidence: 99%